Activity profile in elite Italian soccer team - Vigne, G.; Gaudino, C.; Rogowski, I.; Alloatti, G.; Hautier, C. (International Journal of Sports Medicine, 2010)
The purpose of this study was to analyse the activity profile of players in a top-class team in the Italian national football league over the course of a season (n=388). The effect of playing position and the two halves on the number and duration of short, intense bursts of effort and recovery phases was studied. The main results show that midfielders cover significantly more distance than players in other positions (p<0.001). For midfielders, the number of displacements of 2-40 m and the number of sprints covering between 2 and 9 m and between 30 and 40 m are considerably greater than for other positions (p<0.05). The distances covered in the second half compared to the first half are significantly lower for all categories of run (p<0.05). In the second half, the distance covered at very high intensity is significantly lower (p<0.01), whilst the number of recovery times greater than 120 s increases significantly compared to the first half (p<0.01). This study provides data which could be used as a basis for the work of scientists as well as football professionals.